Microbiological aetiology of paediatric respiratory tract infections in Kyrgyzstan - Nargiza Osmonbaeva; Joakim Bloch; Aidai Erkinbaeva; Aigerim Tilebalieva; Raisa Tolobekova; Meerim Zhaparova; Aichatou Rogbo-Bengtsson; Elvira Isaeva; Azamat Akylbekov; Maamed Mademilov; Erkingul Baltabaeva; Gulbarchyn Esengeldieva; et al. (BMC Infectious Diseases)
Abstract Introduction Respiratory tract infections (RTIs) are a leading cause of morbidity and mortality in children worldwide. Aetiologic virus and bacteria vary geographically. To date, no systematic data on RTI aetiologies have been published from Kyrgyzstan, a country with a high under-five mortality from lower RTIs and a widespread overuse of antibiotics. We aimed to identify the aetiologies of RTI in children in Kyrgyzstan and to assess the pneumococcal conjugate vaccine (PCV) vaccination rate and the correlation with the detection of Streptococcus pneumoniae in our population. Methods We collected samples from children aged 6 months to 12 years presenting with symptoms of acute RTI for outpatients or diagnosed with pneumonia for inpatients. Samples were collected from November 2022 to June 2023 and were analysed using standard culture methods and real-time polymerase chain reaction (RT-PCR) to identify bacterial, viral, and atypical bacterial pathogens. We obtained the vaccination status through vaccination records and parents’ recollections. Results Positive bacteriologic cultures were found for 294 (25.0%) of 1174 outpatients and 83 (27.7%) of 300 inpatients. S. pneumoniae was the most commonly found bacterial pathogen in both groups, making up 44.8% of all cultured bacteria. Furthermore, 445 (64.1%) of 694 outpatients with RT-PCR performed had one or more viral pathogens identified, while this was the case for 162 (54.7%) of 296 inpatients. Mycoplasma pneumoniae was identified in 15.8% of inpatients possibly representing an epidemic in the spring of 2023. Approximately 20% of both in- and outpatients had a viral-bacterial simultaneous detection. 87.1% of outpatients and 75.9% of inpatients had been vaccinated with PCV. We found a higher proportion of unvaccinated children among those under five years of age and a higher carriage rate of S. pneumoniae among unvaccinated inpatients. Conclusion In this study, we found a high prevalence of viral infections and viral-bacterial simultaneous detections among Kyrgyz children with respiratory tract infections (RTI). The findings from this study can inform new clinical guidelines for local health workers and lead to more targeted use of antibiotics and improved health outcomes for children in Kyrgyzstan. Clinical Trial Not applicable.